MEDICAL GEOGRAPHIC SITUATION OF KASHKADARYA REGION - Narzullayev, Husniddin Asliddin o‘g‘li (Educational Research in Universal Sciences, 2024)
In this article, medical geographical situations in Kashkadarya region are studied and analyzed. In the assessment of the medical and ecological situation in the region, issues such as air, water, and soil pollution and their impact on human health, as well as the impact of climate change on the population were deeply analyzed and suggestions and recommendations were developed.